Uncommon abdominal pain: A case report on spontaneous superior mesenteric artery dissection (Indian Journal of Case Reports, 2024)
Spontaneous isolated superior mesenteric artery dissection (SISMAD) is a rare cause of abdominal pain, with symptoms ranging from incidental discovery to severe complications, such as acute bowel ischemia or a potentially fatal rupture of a superior mesenteric artery aneurysm. First reported in 1946, SISMAD is an uncommon vascular condition, accounting for <0.06% of acute abdominal pain cases. This case involves a 52-year-old male presenting with abdominal pain, diagnosed with SISMAD through imaging without evidence of bowel ischemia. Non-invasive imaging techniques, such as computed tomography angiography or magnetic resonance angiography, are crucial for diagnosing SISMAD. In this instance, a conservative treatment approach, including bowel rest and anticoagulation, was successful. The increased detection of SISMAD due to advanced imaging techniques necessitates its consideration when common causes of acute abdomen are excluded. Management strategies, in the absence of standardized guidelines, range from conservative care and anticoagulation to endovascular stenting or open surgical repair. Despite its rarity, SISMAD poses significant risks for morbidity and mortality.